Adult Food Protein-Induced Enterocolitis Syndrome - Anvari, Sara; Ruffner, Melanie A. (Frontiers in Allergy, 2022)
Food protein-induced enterocolitis syndrome (FPIES) is a non-IgE, cell-mediated food allergy, commonly diagnosed in infants and young children. In recent years, new-onset adult FPIES has been recognized. The underlying pathogenic mechanism of FPIES has yet to be elucidated, thus disease-specific diagnostic biomarkers have yet to be determined and an oral food challenge (OFC) remains the gold-standard for the diagnosis. Pediatric patients with FPIES classically present with symptoms of delayed, repetitive vomiting approximately 1 to 4 hours following ingestion of a food allergen. However, adults with FPIES have been reported to have a different symptom profile and different food triggers compared to the pediatric FPIES population. The current FPIES diagnostic criteria may not be appropriate for the diagnosis of adult FPIES patients, thus an oral food challenge remains a diagnostic tool. This review provides an overview of the current literature on the clinical presentation, epidemiology, diagnosis, triggers and management of adult FPIES.